Emigration and brain drain : evidence from the Caribbean - Mishra, Prachi, 1975- (IMF working paper, 2006)
This paper quantifies the magnitude and nature of migration flows from the Caribbean and estimates their costs and benefits. The Caribbean countries have lost 10-40 percent of their labor force due to emigration to OECD member countries. The migration rates are particularly striking for the highskilled. Many countries have lost more than 70 percent of their labor force with more than 12 years of completed schooling-among the highest emigration rates in the world. The region is also the world's largest recipient of remittances as a percent of GDP. Remittances constituted about 13 percent of the region's GDP in 2002. Simple welfare calculations suggest that the losses due to high-skill migration (ceteris paribus) outweigh the official remittances to the Caribbean region. The results suggest that there is indeed some evidence for brain drain from the Caribbean.